IPCs for HLB Prevention in Young Trees - Alferez, Fernando; Gaire, Susmita; Albrecht, Ute; Batuman, Ozgur; Qureshi, Jawwad; Zekri, Mongi (EDIS, 2019)
Controlling the Asian citrus psyllid vector of huanglongbing (HLB) is critical especially in young trees. Reducing HLB incidence is essential for tree survival and productivity under current endemic conditions. Individual protective covers (IPCs) are a novel strategy based on psyllid exclusion by means of a protective mesh bag. In this article we report on the results obtained in our 18-month trial on IPCs. Peer reviewed through UF/IFAS Citrus Research and Education Center; published in Citrus Industry Magazine.